The Concept of Islamic Education Collaboration with the Education of the Dutch East Indies in Ahmad Dahlan's Perspective - Nanik Mindarnengsih; Istikomah Istikomah; Tuafiq Churrohman (Proceedings of The ICECRS, 2020)
The entry of Islamic education in Indonesia, it is very appropriate to trace the entry of Islam in Indonesia, because education in Indonesia has the same historical journey with the history of the entry of Islam in Indonesia. Education in the Dutch East Indies era had a mission towards the ability to master the Dutch language in order to facilitate communication between pribumi (Indonesian people) and the Dutch. The method used in this research is descriptive qualitative, descriptive is used to be able to understand and provide a detailed description of the problems in the focus of research, using data analysis techniques in the form of library research (library research). This research results that traditional Islamic education with modern Islamic education systems through the process of integrating the two fields of science both philosophically, curriculum, methodology, management, even to the department.